First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa) - Vieira, Leandro M.; Gordon, Dennis P.; Correia, Monica D. (Zootaxa, 2007)
The genus Vasignyella Gordon, 1989 is recorded for the first time from the Atlantic Ocean, in the littoral zone of Alagoas, northeastern Brazil. It is only the second species attributed to the genus, the type species of which has never been seen in a reproductive state, and which has a colony form of uniserial chains of unizooidal internodes. The new species from Brazil, herein described as V. ovicellata, has a similar colony form in the infertile state, but has ovicells in multizooidal internodes. This character allows a reconsideration of the phylogenetic relationships of Vasignyella, which was previously the sole included genus in the catenicellid bryozoan subfamily Vasignyellinae. The nearest generic relative of Vasignyella was, however, considered to be the extinct genus Ditaxiporina Stach, 1935 (subfamily Ditaxiporinae), with near-identical autozooidal morphology, but with most internodes multizooidal and also having ovicells when reproductive. The discovery of ovicells in Vasignyella allows the subfamily Vasignyellinae to be discarded and the genus transferred to the Ditaxiporinae, a subfamily with an Atlanto-American record previously known to range from the Late Paleocene to the Early Oligocene.